2011
DOI: 10.1088/0022-3727/44/35/355401
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity measurement of porous silicon by the pulsed-photothermal method

Abstract: Thermal properties of two types of porous silicon are studied using the pulsed-photothermal method (PPT). This method is based on a pulsed-laser source in the nanosecond regime. A 1D analytical model is coupled with the PPT technique in order to determinate thermal properties of the studied samples (thermal conductivity and volumetric heat capacity). At rst, a bulk single crystal silicon sample and a titanium thin lm deposited on a single crystal silicon substrate are studied in order to validate the PPT metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…28 Therefore, the C p values reported for c-Si as a function of temperature have been used. To solve Eq.…”
Section: à2mentioning
confidence: 99%
“…28 Therefore, the C p values reported for c-Si as a function of temperature have been used. To solve Eq.…”
Section: à2mentioning
confidence: 99%
“…Hence, a large amount of research work has focused on realizing porous silicon (PSi) based optoelectronic devices, such as light emitting diodes (LED) [8], waveguides [9], optical filters [8], thermal isolators [10], photovoltaic diodes [11], and different types of sensors [12]. The Au/PSi structure can be used as a hydrogen fuel cell or for other applications that require tuneable and lower thermal diffusivity than silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Since the porosity of the etched layer reached up to 70 % (see Fig. 1), the equation 4 (κ c-Si = 140 W•m −1 •K −1 was taken from [7]). Table 1 presents a comparison of the values of thermal conductivity for n-type porous silicon obtained by different authors and by different methods.…”
Section: Resultsmentioning
confidence: 99%
“…Strong diameter dependence of thermal conductivity in the nanowires was ascribed to the increased phonon-boundary scattering and possible phonon spectrum modification. Experimental studies using the pulsed-photothermal method revealed that the thermal conductivity of macroporous and mesoporous silicon is two times lower than that of the single crystal silicon (140 W•m −1 •K −1 ) [7]. Thermal conductivities of sintered porous silicon films measured at room temperature using a non-contact method based on lock-in thermography ranged from 21 to 2.3 W•m −1 •K −1 ) and decreased with increasing porosity [8].…”
Section: Introduction * * * *mentioning
confidence: 99%